Restoration of supraspinatus and infraspinatus deep plane occupation ratios was greater in delaminated tears than in non-delaminated tears after rotator cuff repair - Yoon, Sung-Hyun (J Orthop, 2020)
Total 132 patients who underwent arthroscopic suture bridge repair were divided into two groups: group A, non-delaminated tears; group B, deep layer, more retracted, delaminated tears. In addition, group B were divided into two subgroups: group I (≤2-cm) and group II (>2-cm). Muscle volume was evaluated by measuring the occupation ratio and restoration of the rotator cuff muscle was defined as the difference between the preoperative and postoperative occupation ratios. The restoration of the SS and IS deep plane occupation ratios was greater in >2-cm-sized delaminated tears than in ≤2-cm-sized delaminated and non-delaminated tears.